Sustainable Lifestyle: Indonesian Consumer's Behavior Toward Sustainable Fashion Consumption - Kurniaty, Dewi; Subagio, Aris; Simatupang, Ayu Andriani; Nursaffanah, Nada Fathimah (Pusat P2M Politeknik Negeri Batam, 2024)
This study investigates Indonesian consumer behavior towards sustainable fashion consumption, particularly focusing on thrift shopping, using the SHIFT framework (Social Influence, Habit Formation, Individual Self, Feelings and Cognition, and Tangibility). A cross-sectional, quantitative approach was employed, collecting data from 155 respondents through online surveys and social media discussions. The study used binary logistic regression to assess the impact of factors such as age, income, shopping preferences, and the use of TikTok for gathering information about thrifting. Results revealed that only the use of TikTok significantly influences thrifting intentions, while other factors like age, income, and shopping methods were not significant. Additionally, social media discussions reflected strong public disagreement (96.9%) with the government's 2023 ban on imported second-hand clothing, with most respondents engaged in thrifting for its economic and environmental benefits. The study concludes that social influence, particularly through platforms like TikTok, plays a vital role in promoting sustainable consumption practices in Indonesia.